Tumor Associated Macrophages in Kidney Cancer. (11th October 2016) - Kovaleva, Olga V.; Samoilova, Daria V.; Shitova, Maria S.; Gratchev, Alexei
Abstract : Tumor associated macrophages (TAMs) are an important element of tumor stroma. They originate from blood monocytes attracted by chemokines and cytokines produced by tumor cells and, being instructed by tumor microenvironment, develop into potent tumor-supporting cell population. TAMs were demonstrated to directly stimulate tumor cell proliferation and to promote angiogenesis. Further TAMs provide for efficient immune escape by producing immunosuppressive cytokines and facilitate tumor dissemination by producing extracellular matrix remodeling enzymes. In renal cell carcinoma (RCC), numerous studies were performed for elucidation of the role of TAM in tumor progression. Using pan-macrophages marker CD68 and type 2 macrophage (M2) markers CD163 and CD206, it was demonstrated that increased density of TAMs is associated with poor survival of patients. Although most of the studies are focused on M2 population in RCC, several markers rather typical for type 1 macrophages (M1) were also characterized. Macrophages isolated from RCC tumors were shown to produce proinflammatory cytokines TNFα, IL-1 β, IL-6, and CCL2. It can be concluded that RCC is an excellent example of a tumor with hybrid phenotype of TAMs that share both M1 and M2 properties. Moreover, TAMs seem to be an attractive therapeutic target as well. Further investigations are needed for identification of RCC-specific TAM markers with high predictive capacity and/or suitable for therapeutic targeting.